2013
DOI: 10.3389/fpsyg.2013.00648
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous visual exploration creates developmental change in familiarity and novelty seeking behaviors

Abstract: What motivates children to radically transform themselves during early development? We addressed this question in the domain of infant visual exploration. Over the first year, infants' exploration shifts from familiarity to novelty seeking. This shift is delayed in preterm relative to term infants and is stable within individuals over the course of the first year. Laboratory tasks have shed light on the nature of this familiarity-to-novelty shift, but it is not clear what motivates the infant to change her exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
59
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 46 publications
5
59
0
Order By: Relevance
“…These results are interpreted as evidence that the infants in this group showed stronger novelty preference than the infants with cord Pb ≥ 2.00 μg/dL. Perone and Spencer (2013) proposed that novelty preference provides evidence that a robust memory for the familiar stimuli has been formed and that the infants have started to learn new items. Accordingly, the results imply that those infants with cord Pb < 2.00 μg/dL had built a more robust memory of their mother's voice and had started encoding the information for a novel voice than the other infants.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…These results are interpreted as evidence that the infants in this group showed stronger novelty preference than the infants with cord Pb ≥ 2.00 μg/dL. Perone and Spencer (2013) proposed that novelty preference provides evidence that a robust memory for the familiar stimuli has been formed and that the infants have started to learn new items. Accordingly, the results imply that those infants with cord Pb < 2.00 μg/dL had built a more robust memory of their mother's voice and had started encoding the information for a novel voice than the other infants.…”
Section: Discussionmentioning
confidence: 87%
“…We can infer that the infants in group 1 showed a preference for novel stimuli, whereas infants in group 2 had a bias toward familiar stimuli. Previous studies have shown that infants gradually shift their preference for familiarity to novelty during the first year of life (Fantz, 1964; Perone & Spencer, 2013; Rose, Feldman, & Jankowski, 2004). Thus, the above difference between groups 1 and 2 might suggest a delay in the familiarity-novelty shift in group 2.…”
Section: Discussionmentioning
confidence: 99%
“…A variant of the dynamic model presented here has been used to simulate infants’ performance in the processing speed task (Perone & Spencer, 2013, 2014). These simulations suggest that individual and developmental differences could be realized through the same type of mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…These excitatory traces built up slowly with experience, which allowed for distribution across the feature dimension through varying experiences. Following this autonomous development, Perone and Spencer (2013) tested these individual “infants” (i.e., models with individual developmental histories) in the processing speed task. These simulations showed that this accumulation of experience provided the typical developmental improvements: “older” models with more experience encoded items in to memory more quickly and showed faster shift rates (cf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation